Penyesuaian Diri Orang Tua Dalam Menghadapi Anak Autisme - cindy alvaresha; wahidah fitriani; putri yeni (Program Studi Bimbingan dan Konseling, 2023)
Autism is a complex developmental disorder that involves communication, social interaction and imaginative activities. The cause of the birth of children with autism is largely determined by genetic factors, disorders of the nervous system, chemical imbalances, and other possibilities such as infections that occur before and after birth which result in damage to the child's brain. This study aims to find out how parents adjust themselves to children with autism. This study uses a qualitative method with a literature review. The results of the study show the adjustment of parents to children with autism. Here it is still seen that parents have not been able to adjust themselves to autism child. Parents must be able to accept the fact that their child has autism, otherwise the impact will be very bad, because this will only make children with autism feel not understood and not accepted for who they are.